Metastatic adenocarcinoma of mammary‐like glands of the vulva successfully treated with surgery and hormonal therapy. Issue 1 (6th July 2012) - Benito, Virginia; Arribas, Sara; Martínez, David; Medina, Norberto; Lubrano, Amina; Arencibia, Octavio
Abstract Vulvar cancer is a rare malignancy; most tumors are squamous cell type while adenocarcinomas are rare. Primary adenocarcinomas of the vulva predominantly include extramammary Paget's disease and sweat gland carcinomas. Greene first described a rare form of adenocarcinoma in 1936, which was called adenocarcinoma of mammary‐like glands of the vulva because of its morphologic and immunohistochemical resemblance to breast adenocarcinomas. In the management of this entity, varying combinations of surgery, radiation therapy, systemic chemotherapy and/or hormonal therapy may be used, as in patients with orthotopic breast carcinoma. However, hormonal therapy leads the way in patients with positive hormonal receptors, where other therapies cannot be used due to comorbidities or advanced age. We present the first reported case of an elderly patient with metastatic vulvar adenocarcinoma arising from mammary‐like glands, successfully treated with a combination of surgery and hormonal therapy.